ANTENATAL CARE VISIT COMPLIANCE IN THE TANJUNG BERLIAN HEALTH CENTER WORK AREA - Ni Nyoman Wartinah; Roni Aldiano (Universitas Batam, 2021)
Background : Non-compliance in prenatal care can cause the mother's complications to be unrecognized which may affect pregnancy or pregnancy complications so that they cannot be resolved immediately. Detection during antenatal care is very helpful in preparation for risk control (Manuaba, 2007). Moreover, pregnant women who do not perform antenatal care, it will not be known whether the pregnancy is going well or experiencing high risk conditions and obstetric complications that can endanger the life of the mother and her fetus. And it can cause high morbidity and mortality (Prawiroharjo, 2008). One of the factors that influence the high maternal mortality rate is the attitude and behavior of the mother herself during pregnancy and is supported by the mother's knowledge of her pregnancy. Some of the factors behind the risk of maternal death are the lack of community participation due to the low level of maternal education, low family economic capacity, and unsupportive socio-cultural position. If taken further, some of these unsupportive behaviors can also carry risks. Other factors such as maternal age at pregnancy and childbirth, mothers who are too young (less than 20 years) and too old (over 35 years), frequency of births having given birth four times or more and spacing between births or deliveries of less than 24 months, including groups that are at high risk and increase the chance of maternal death are getting bigger (Erina, 2012). Research Objectives Knowing the Compliance of Antenatal Care Visits in the Tanjung Berlian Public Health Center. Method :This research uses descriptive study. The population used in this study were all pregnant women in the 3rd trimester in the Tanjung Berlian Public Health Center, totaling 206 people. The sampling method was taken using purposive sampling technique, which is purposive sampling in accordance with the required sample requirements / criteria